Healthy lifestyle factors and recurrent cardiovascular events in patients with OSA: the SAVE study - You, Shoujiang; Zheng, Danni; Loffler, Kelly A.; McEvoy, R. Doug; Li, Qiang; Luo, Yuanming; Barbé, Ferran; Ou, Qiong; Chen, Rui; Liu, Chun-feng; Cao, Yongjun; Wang, Xia; et al. (BMC medicine, 2025)
The extent to which healthy lifestyle factors influence recurrent cardiovascular events in obstructive sleep apnea (OSA) patients is uncertain. To evaluate the association between adherence to baseline healthy lifestyle and the risk of recurrent cardiovascular events in OSA patients. Post hoc analyses of the Sleep Apnea Cardiovascular Endpoints (SAVE) study involving participants with moderate-to-severe OSA and established cardiovascular disease (CVD) who were randomized to continuous positive airway pressure (CPAP) plus usual care or usual care alone. We assigned a score ranging from 0 to 4 for each participant, based on the number of criteria met for the baseline health lifestyle factors of non-smoking, moderate-to-vigorous physical activity, ideal waist/hip ratio, and low-to-moderate alcohol consumption. In total, 2659 OSA patients with established CVD were included. The adjusted hazard ratios for participants with ≥ 2 healthy lifestyle factors compared with none were 0.64 (95% confidence interval [CI] 0.50-0.84) for composite cardiovascular events, 0.46 (0.28-0.74) for stroke, 0.65 (0.45-0.96) for hospitalization for unstable angina, 0.35 (0.19-0.63) for all-cause mortality, and 0.36 (0.16-0.79) for CVD death during a mean follow-up of 3.7 years. Each increment in healthy lifestyle factor score was associated with reduced risk of composite and separate cardiovascular events. A trend was found showing greater CPAP treatment benefit in those with more baseline healthy lifestyle for myocardial infarction and all-cause mortality; however, it did not reach statistical significance. Greater adherence to an overall baseline healthy lifestyle is significantly associated with a lower risk of recurrent composite cardiovascular events in OSA patients with established CVD.